Preferencias y satisfacción de mujeres sobre tamizaje de VPH con pruebas moleculares en establecimientos públicos de salud en Iquitos, Loreto, 2024 - Alegria Zvietcovich, Norma Yanilitt (2025)
Objective: To describe the sociodemographic characteristics, preferences, and satisfaction of women regarding HPV molecular screening, and to analyze their relationship with sociodemographic factors in public health establishments in Iquitos, Loreto, during 2024. Methods: Quantitative, observational, analytical, and cross sectional study. A total of 186 women aged 30–49 who underwent HPV molecular testing at the IPRESS San Juan and IPRESS Progreso health centers were surveyed. Results: The mean age was 39 years; most were cohabiting, with primary education and informal occupations. A total of 65.1% performed self-sampling, valuing its ease, autonomy, and privacy. Although 55.4% initially preferred assisted sampling, overall satisfaction was high: over 75% rated the service positively and 98.9% would participate again. A significant association was found between preference for self-sampling and variables such as health center, education, occupation, and number of children (p < 0.05). Satisfaction was significantly associated with health center and marital status (p < 0.05). Conclusions: Self sampling is an accepted and feasible strategy to expand HPV screening coverage, particularly among women with lower education, informal occupations, and fewer children. Satisfaction was higher among women from San Juan and those who were married or single, highlighting the influence of contextual and relational factors.